A Special Issue of the Canadian Journal of Learning and Technology on Knowledge Building - Michele Jacobsen (The Canadian Network for Innovation in Education (CNIE), 2010)
In a pervasive media and technology landscape that is increasingly global, participatory and connected, one in which learners and teachers can increasingly become creators of knowledge rather than mere consumers of prepared messages and ideas, it is vital for the field of educational technology to take stock of the latest research on knowledge building. Marlene Scardamalia and Carl Bereiter, innovative pioneers in the area of Knowledge Building in education, define the construct of Knowledge Building as having several characteristics that distinguish it from constructivist learning in general. Two key characteristics of Knowledge Building are intentionality and community knowledge. Intentionality captures that people engaged in knowledge building know they are doing it and that advances in knowledge are purposeful. Community knowledge captures that while learning is a personal matter, knowledge building is done for the benefit of the community. Scardamalia and Bereiter emphasize that in contrast to being spontaneous, a knowledge building culture requires a supportive learning environment and teacher effort and artistry to create and maintain a community devoted to ideas and to idea improvement. Distinct from improving individual students' ideas and understanding, the collective work of Knowledge Building is explicitly focused on the creation and improvement of knowledge of value to one's community - advancement of the knowledge itself.